Author correction: P53 and mTOR signalling determine fitness selection through cell competition during early mouse embryonic development - Bowling,S; Di,Gregorio A; Sancho,M; Pozzi,S; Aarts,M; Signore,M; Schneider,MD; Martinez-Barbera,JP; Gil,J; Rodriguez,TA (Nature Communications, 2018)
The original version of this Article contained an error in the spelling of Juan Pedro Martinez-Barbera, which was incorrectly given as Juan Pedro Martinez Barbera. This error has now been corrected in both the PDF and HTML versions of the Article.